2010
DOI: 10.1016/s0083-6729(10)83009-2
|View full text |Cite
|
Sign up to set email alerts
|

Alarm Pheromones—Chemical Signaling in Response to Danger

Abstract: In this chapter we discuss our current understanding of chemical alarm signaling in a variety of animal groups (including social and pre-social insects, marine invertebrates, fish, and mammals) and in plants. We also briefly discuss the exploitation of alarm pheromones as foraging cues for natural enemies. We conclude with a brief discussion of the potential exploitation of alarm signaling to achieve the applied goal of managing pest species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 138 publications
0
64
0
1
Order By: Relevance
“…The binding properties of three classical pea aphid OBPs ( ApisOBP1 , ApisOBP3 and ApisOBP8 ) have been investigated using 12 chemical compounds [29]. Research has confirmed that OBPs are keys in the perception of (E)-β-farnesene (EβF), an aphid alarm pheromone widely used in olfaction-based approaches to control aphid populations [30]. The chemical can interfere with an insect’s ability to find suitable hosts or olfactory cues regarding natural enemies, and has been used successfully in the “push–pull” pest control strategy [31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…The binding properties of three classical pea aphid OBPs ( ApisOBP1 , ApisOBP3 and ApisOBP8 ) have been investigated using 12 chemical compounds [29]. Research has confirmed that OBPs are keys in the perception of (E)-β-farnesene (EβF), an aphid alarm pheromone widely used in olfaction-based approaches to control aphid populations [30]. The chemical can interfere with an insect’s ability to find suitable hosts or olfactory cues regarding natural enemies, and has been used successfully in the “push–pull” pest control strategy [31, 32].…”
Section: Introductionmentioning
confidence: 99%
“…It has been established for a few decades that animals (from insects to mammals) are able to communicate through body “odor,” not only reproductive state, but also socially relevant emotions like alarm [1], fear [2], aggression [3], anxiety [4]. These chemosensory signals (pheromones) induce corresponding physiological and behavioral adaptations within surrounding conspecifics.…”
Section: Introductionmentioning
confidence: 99%
“…The significant decrease in locomotory activity by dispersers when exposed to soldiers’ anal droplets can be interpreted as an adaptive response because a slower evasive behaviour could benefit their fitness (Verheggen et al. ). Although the mean time spent in the zone could suggest a potential attraction, it is also true that this was not reflected in the cumulative time spent inside the zone, as would be expected.…”
Section: Discussionmentioning
confidence: 99%
“…By analogy, soldiers should perform more aggressively and with a more alert searching behaviour in the quest for enemies (Blum ; Bell ; Verheggen et al. ), which can be translated into larger distances moved. We are aware that the latter could be interpreted as an effect of chaotic fleeing as well.…”
Section: Discussionmentioning
confidence: 99%